The Influence of Hedonic Shopping Motivation, Ease of Use, Customer Reviews, and Electronic Word of Mouth on Impulse Buying Behavior at Shopee E-Commerce During The COVID-19 Pandemic - Mirahanda, Theresia Angel; Parmariza, Yennida (Universitas Mercu Buana, 2024)
This study aims to determine, analyze, and explain the effect of hedonic shopping motivation, ease of use, customer reviews, and electronic word of mouth on impulse buying behavior at E-commerce Shopee during the COVID-19 pandemic. The approach used in this research is descriptive method and quantitative approach. The data analysis method in this study uses Partial Least Square (PLS) and data collection in this study uses a survey method, with the research instrument used is a questionnaire. The population in this study are people who shop using Shopee, the number of which is not known with certainty. The sample used in this study was 211 respondents, with the sampling technique using purposive sampling. The results of this study indicate that hedonic shopping motivation has a positive and significant effect on impulse buying behavior; customer reviews have a positive and significant effect on impulse buying behavior; electronic word of mouth has a positive and significant effect on impulse buying behavior; ease of use has no effect on impulse buying behavior.